Toponymy and its aspects in naming villages as tourism destinations in Madura: An ethnolinguistics perspective - Ayuningtias, Diah Ikawati; Ekawati, Rosyida (Englisia Journal, 2024)
This study is intended to analyze the category of toponyms of tourism destinations in Bangkalan, Madura in particular the four villages where the tourism destinations exist based on the aspect of the naming system. Then, it identifies the relation between the toponym with the cultural values of the names of those tourism destinations.  This study used a descriptive qualitative method. The data are names of the villages in Kamal, Socah, and Bangkalan districts in which there are four tourism villages. The data collection was carried out by observing, interviewing the head of the villages, and reviewing the document of villages for tourism destinations. Results of the study show that there are three aspects of toponymy in the four tourism villages. They are toponymy of vegetation, history, and embodiment. There is no regional toponymy. From the aspect of naming the villages, it can provide important cultural and historical moments representing the people's lives, religious, and linguistic creativity. The place name is not merely arbitrary but depends on various factors or aspects and provides linguistic and cultural information toward the name of the four tourism villages in this study.